Protocol for CRISPR-based manipulation and visualization of endogenous α-synuclein in cultured mouse hippocampal neurons - Leonardo A. Parra-Rivas; Rohan Sharma; Trinity E. Rust; Hannah O. Bazick; Jared Carlson-Stevermer; Mark J. Zylka; Yuki Ogawa; Subhojit Roy (STAR Protocols)
Summary: CRISPR-Cas9 technology enables acute gene knockdown and endogenous tagging to study single-synapse function. Here, we present a protocol for depleting alpha-synuclein (α-syn) or visualizing native α-syn with an endogenously inserted fluorescent tag in cultured mouse hippocampal neurons. We describe detailed steps, including CRISPR design, virus packaging/transduction (delivery), and validation of on-/off-target editing. This protocol should be useful for assigning precise function to contentious synaptic proteins and for visualizing protein trafficking without overexpression in cultured hippocampal neurons—an established model system for synaptic biology.For complete details on the use and execution of this protocol, please refer to Parra-Rivas et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.